Polymorphisms in the Hsp70 gene locus are genetically associated with systemic lupus erythematosus - Fuernrohr, Barbara G.; Wach, Sven; Kelly, Jennifer A.; Haslbeck, Martin; Weber, Christian K.; Stach, Christian M.; Hueber, Axel J.; Graef, Daniela; Spriewald, Bernd M.; Manger, Karin; Herrmann, Martin; Kaufman, Kenneth M.; et al. (Annals of the Rheumatic Diseases, 2010)
Background: Heat shock proteins (Hsps) play a role in the delivery and presentation of antigenic peptides and are thought to be involved in the pathogenesis of multifactorial diseases. Objective: To investigate genes encoding cytosolic Hsp70 proteins for associations of allelic variants with systemic lupus erythematosus (SLE). Methods: Case-control studies of two independent Caucasian SLE cohorts were performed. In a haplotype-tagging single-nucleotide polymorphism approach, common variants of HspA1L, HspA1A and HspA1B were genotyped and principal component analyses were performed for the cohort from the Oklahoma Medical Research Foundation (OMRF). Relative quantification of mRNA was carried out for each Hsp70 gene in healthy controls. Conditional regression analysis was performed to determine if allelic variants in Hsp70 act independently of HLA-DR3. Results: On analysis of common genetic variants of HspA1L, HspA1A and HspA1B, a haplotype significantly associated with SLE in the Erlangen-SLE cohort was identified, which was confirmed in the OMRF cohort. Depending on the cohorts, OR ranging from 1.43 to 1.88 and 2.64 to 3.16 was observed for individuals heterozygous and homozygous for the associated haplotype, respectively. Patients carrying the risk haplotype or the risk allele more often displayed autoantibodies to Ro and La in both cohorts. In healthy controls bearing this haplotype, the amount of HspA1A mRNA was significantly increased, whereas total Hsp70 protein concentration was not altered. Conclusions: Allelic variants of the Hsp70 genes are significantly associated with SLE in Caucasians, independently of HLA-DR3, and correlate with the presence of autoantibodies to Ro and La. Hence, the Hsp70 gene locus appears to be involved in SLE pathogenesis.